Advances in optical surface texture metrology - Leach, R. K. (IOP series in emerging technologies in optics and photonics., 2020)
Advances in Optical Surface Texture Metrology covers the latest advances in the development of optical surface texture measuring instruments. Rather than concentrate on the basic principles of the optical measurement methods, this book takes a deeper dive into the operation of the instruments and the new application areas where they can be applied, with an emphasis on advanced manufacturing. Latest advances discussed will include the drive towards faster instruments for in-process applications, the ability to measure highly complex surfaces (in e.g. additive manufacturing) and advances in the use of machine learning to enhance data analysis. Part of IOP Series in Emerging Technologies in Optics and Photonics.